Isabel and her colores go to school - Alessandri, Alexandra (Sleeping Bear Press, 2021)
"English just feels wrong to Isabel. She prefers her native Spanish. As she prepares for a new school, she knows she's going to have to learn. Her first day is uncomfortable, until she employs her crayons and discovers there's more than one way to communicate with new friends"--